2019
DOI: 10.32604/sv.2019.06523
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Sound Absorption Properties of Flexible Polyurethane (PU) Foam using Nanofibers and Nanoparticles

Abstract: Polyurethane foam as the most well-known absorbent materials has a suitable absorption coefficient only within a limited frequency range. The aim of this study was to improve the sound absorption coefficient of flexible polyurethane (PU) foam within the range of various frequencies using clay nanoparticles, polyacrylonitrile nanofibers, and polyvinylidene fluoride nanofibers. The response surface method was used to determine the effect of addition of nanofibers of PAN and PVDF, addition of clay nanoparticles, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Hajizadeh et al have found that the use of a combination of nanoclay particles, polyacrylonitrile nanofibers (NFs), and PVDF NFs could synergistically improve the SAC of flexible PU foam by more than twice in the middle frequency region. [97] They have ascribed the phenomenon to the large specific surface characteristics of fillers. Tiuc et al have mixed synthetic textile fibers (including nylon, polyacril, and modal) with PU foam.…”
Section: Physical Blending Modificationmentioning
confidence: 99%
“…Hajizadeh et al have found that the use of a combination of nanoclay particles, polyacrylonitrile nanofibers (NFs), and PVDF NFs could synergistically improve the SAC of flexible PU foam by more than twice in the middle frequency region. [97] They have ascribed the phenomenon to the large specific surface characteristics of fillers. Tiuc et al have mixed synthetic textile fibers (including nylon, polyacril, and modal) with PU foam.…”
Section: Physical Blending Modificationmentioning
confidence: 99%
“…The outer topography of the foams is almost open cell as the gases on the outer surface will have an atmospheric effect [20]. Few SEM analysis reports have shown that rigid foams are a combination of both open and closed cells in cell structure [21].…”
Section: Figure 1 Process and Formation Of Polyurethane Foammentioning
confidence: 99%
“…After the sound wave entered composite samples, due to the porous structure of IBPIF, the sound wave would continue to reflect and propagate inside, resulting in the vibration of the air inside the sample, causing friction between air molecules and friction between air molecules and the cell wall to convert a part of sound energy into heat energy. [30,[36][37][38] In addition, because IBPIF was filled in the separated core of ARHC, IBPIF was surrounded by honeycomb walls of pure aramid. Therefore, during the sound wave propagation, the honeycomb wall also played a certain role in reflection and increased the propagation path of the sound wave inside the sample, and finally achieved the absorption for the sound wave.…”
Section: Sound Absorption Performance Of Composite Materialsmentioning
confidence: 99%